(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The ageing process is of course a biological reality which has its own dynamics, largely beyond human control. Ageing can generally be described as the process of growing old and is an intricate part of the life cycle. A major demographic issue for India in the 21st century is population ageing with wide implications for economy and society in general. With the rapid changes in demographic indicators over the last few decades, it is certain that India will move from being a ‘young country’ to an ‘old country’ over the next few decades. The ageing population that was 7.5 (77 million) of the total population in 2001 increased to 8.6 (104 million) by 2011. People can be considered old because of certain changes in their activities or social roles. Also old people have limited regenerative abilities and are more prone to disease, syndromes, and sickness as compared to other adults. The medical study of the aging process is called gerontology and the study of diseases th at afflict the elderly is geriatrics.